Towards a power consumption estimation model for routers over TCP and UDP protocols - Mohammed, Ali Qusay (2015)
Due to the growing development in the information and communication technology (ICT) industry, the usage of routers has increased rapidly. Meanwhile, these devices that are produced and developed today consume a definite amount of power, Furthermore, with limited focus on power estimation techniques and the increased demands of networking devices, it led to an increase of the vitality consumption as a result. While new high capacity router components are installed, energy intake in system elements will be rising due to the higher capability network consuming larger component of the vitality. This study considers providing estimating power model in different traffic settings over TCP and UDP protocols, this study is mainly concerned about the transport protocols power consumption. Isolating the power consuming components within an electronic system is a very precise process that requires deep understanding of the role of each component within the system and a thorough study of the component datasheet. The study started by simulating the protocols mechanism then followed by protoclos power measurements, a simple simulation has been provided for Xilinx Virtex-5, it is very complicated to simulate the whole system due to the need of an external devices, so the simulation focused on wavelengths, frequencies and traffic types. This study found that the estimated power stokes was high when the 1480nm, 1580nm, and 1750nm power source increase. while there were differrence in the consumed power while transiting different types of traffic such as CBR and HTTP through UDP and TCP. The effect of different frequencies has been noticed also while applying different frequencies to the protocols. So it is believed that this study may enhance the power scenarios in the network and routers throug applying different techniques to UDP and TCP